Results of less radical fertility-sparing procedures with omitted parametrectomy for cervical cancer: 5years of experience - Slama, Jiri; Cerny, Andrej; Dusek, Ladislav; Fischerova, Daniela; Zikan, Michal; Kocian, Roman; Germanova, Anna; Cibula, David (Gynecologic oncology, 2016)
OBJECTIVE: The aim of our study was to describe oncological and obstetrical outcomes in patients who underwent less radical fertility-sparing surgical (FSS) procedures with omitted parametrectomy for cervical cancer. METHODS: Included were women with cervical cancer stages IA2-IB2 who were under the age of 40 and desired future pregnancy. Patients underwent pelvic lymphadenectomy and sentinel lymph node biopsy. Node-negative cases underwent subsequent cervical surgery and were further analyzed. Neoadjuvant chemotherapy (NAC) was administered in patients with tumors >2cm and/or involving >2/3 of cervical stroma. Simple vaginal trachelectomy or needle conization were performed according to tumor extent and topography. The follow-up period started once free surgical margins were reached. RESULTS: Out of 44 women enrolled, 32 women (IA2=7, IB1=23, IB2=2) successfully completed FSS. NAC was administered in 9 (28.1%) cases. A simple trachelectomy was performed in 11 patients and needle conization in 21 patients. During the follow-up, 6 out of 32 women became pregnant. Of these, 1 miscarried and 5 successfully delivered. Disease recurred in 6 patients; 5 recurrences were central and 1 recurrence presented as an ovarian mass. Invasive cervical carcinoma, high-grade squamous intraepithelial (HSIL), and low-grade squamous intraepithelial (LSIL) lesions were detected in 4, 1 and 1 patients, respectively. Three of them received NAC. All events were detected within 16months after surgery. CONCLUSIONS: Nearly 27% of patients cannot complete FSS due to node positivity, progression during NAC, or involved margins. The total recurrence rate reached 18.8%, with the majority of invasive recurrences detected in patients after NAC followed by FSS. These patients represent cases at a higher risk of recurrence even if adequate free margins are reached by surgery. Nearly half of the cohort did not consider pregnancy in the near future because of personal reasons.
Keywords: Neoadjuvant Therapy; Trachelectomy; Retrospective Studies; těhotenství; Cervical cancer; konizace děložního čípku; lidé; Adult; mladý dospělý; nádory děložního čípku; zachování plodnosti; Conization; Young Adult; ženské pohlaví; retrospektivní studie; Humans; Pregnancy; neoadjuvantní terapie; Fertility-sparing surgery; Uterine Cervical Neoplasms; adjuvantní chemoterapie; dospělí; Female; Chemotherapy, Adjuvant; trachelektomie; Fertility Preservation